الدولة في النظم الإسلامية - الخواجة، زهير عبدالمجيد; الخواجه، سعدية كريم مهدي (الجامعة الإسلامية, 2023)
إن الدولة مسؤولة أمام الأمة ولا انفصال بينهما، وهما طرفان في عقد واحد هو عقد الخلافة المحكوم بالكتاب والسنة، وإن شهدت بعض العهود خفوت صوت الأمة، وتطاول الدولة، وتسلطها وبخاصة في عهود السيطرة العسكرية واستبداده بالخلافة، فإن ذلك خروج عن الأصل ولا يلغي ويظل التعاقد قائما، ويظل الإسلام موضع المطالبة وأساس المقاضاة بينهما، وهي خصيصة من أبرز خصائص الدولة في الإسلام. ولاحظنا أن الأتراك استولوا على المملكة واستضعفوا الحلفاء، فكان الخليفة كالأسير از سازوا القوه وإن شاورا خلعوم، وإن شاروا قتلوه. بغداد ويذهب أي بلد شاء، وعندما طلب الخليفة سهلة للهر أجاب ملك شاه ولا ساعة راحة تم استولى السلاجية على الخلافة سنة 447ه ومع الهم أعادوا رونق الدولة والخليفة فإن السلطان ملك شاه السلجوقي طلب من الخليفة المقتدر بأمر الله سنة 485ه أن يخرج من وعندما انتقلت الخلافة من بغداد إلى القاهرة على أثر استيلاء التثار على بغداد وقتل الخليفة العباسي دخل الخلفاء تحت وصاية سلاطين المماليك. State is responsible before nation and there is no separation between them. They are two parties in one contract which is the Caliphate Contract governed by the Book and the Sunnah, and although that some eras witnessed fading of the voice of the nation, and the state's extend and control, especially in the eras of military control and its tyranny by caliphate. This is a departure from the principle. It does not cancel the contract which remains valid, and the Islam remains the subject of the claim and the basis for the litigation between them which is one of the most prominent characteristics of the state in the Islam. We noticed that direction of the rightness of the governor through piety and the rightness of the subjects through obedience which is sponsored and encouraged by the state. However, Although the piety of the governor and the obedience of the nation have really the goodness of the situation, claiming nation to be obedient became the first demand of the state's policy. As for the governor and his piety, this is something that the state wanted the nation to demand from the governor by praying to God Almighty.
Keywords: الدولة الإسلامية -- الدعوة الإسلامية -- الكيانات السياسية -- الخلافة الإسلامية